Identifying dominant stakeholder perspectives on urban freight policies: a Q-analysis on urban consolidation centres in the Netherlands - van Duin, Ron; Slabbekoorn, Marijn; Tavasszy, Lori; Quak, Hans (Transport, 2018)
Cities’ sustainability strategies seem to aim at the reduction of the negative impacts of urban freight transport. In the past decades, many public and private initiatives have struggled to gain broad stakeholder support and thus remain viable. Researchers and practitioners have only recently recognised stakeholder acceptance of urban freight solutions as a challenge. A first step in achieving convergence is to understand stakeholder needs, preferences and viewpoints. This paper proposes and applies an approach to identify the main stakeholder perspectives in the domain of urban freight transport. We use Q-methodology, which originates from social sciences and psychology, to record subjective positions and identify the dominant ones. We explain the approach, operationalise the method for the domain of urban freight transport and apply it to stakeholder groups in the Netherlands. We find four dominant perspectives, reflecting how stakeholders normally take positions in the urban freight dialogue. Important findings concern disparities between industry associations and some of their membership, divergent views about the expected role of public administration, and the observation that the behaviour of shippers and Logistics Service Providers (LSP) appears to be inconsistent with their beliefs. All these factors together can act as a barrier to the implementation of urban freight consolidation concepts. The Q-methodology is valuable for eliciting perspectives in urban freight and is a promising tool to facilitate stakeholder dialogue and, eventually, convergence. First Published Online: 4 Sept 2018